Identifikasi Hasil Belajar Siskomdig Karena Efek POE Dibandingkan PRP Pada Siswa SMK - Ines Rendra Kusuma; Setiadi Cahyono Putro; Dila Umnia Soraya (Program Studi bimbingan Konseling PPs UNM Makassar, 2018)
The goals of this research are to find the difference of mean the cognitive and psychomotor learning outcome Simulation and Communication Digital due to implementation of POE learning model compare to learning model PRP . This research is using quasi experimental design through the type of Non-Equivalent Control Group Design. The hypothesist will be tested using Independent Sample of T-test. The result of this research showed that the mean difference test of students' learning outcomes in the cognitive obtained a significance of 0.006, while the psychomotor learning outcomes obtained a significance of 0.000. Based on the results of the average difference, the learning model that is superior to cognitive and psychomotor is the POE learning model.